(untitled) (TSUL LEGAL REPORT, 2026)
This article examines the global nature of anti-corruption, since corruption is one of the negative phenomena of society, which is recognized as a serious crime in the world, and is also an obstacle to the socio-economic development of any country. The legislation and the situation with corruption in some foreign countries are considered as a comparative legal analysis.